Impact of Multidisciplinary Team Management on the Survival Rate of Head and Neck Cancer Patients: A Cohort Study Meta-analysis - Shang, Changyi; Feng, Linfei; Gu, Ying; Hong, Houlin; Hong, Lilin; Hou, Jun (Frontiers in Oncology, 2021)
Background: Head and neck cancer (HNC) is one of the more common malignant tumors that threaten human health worldwide. Multidisciplinary team management (MDTM) in HNC treatment has been introduced in the past several decades to improve patient survival rates. This study reviewed the impact of MDTM on survival rates in patients with HNC compared to conventional treatment methods. Methods: Only cohort studies were identified for this meta-analysis that included an exposure group that utilized MDTM and a control group. Heterogeneity and sensitivity also were assessed. Survival rate data for HNC patients were analyzed using RevMan 5.2 software. Results: Five cohort studies (n = 39,070) that examined survival rates among HNC patients were included. Hazard ratios (HR) were calculated using the random effect model. The results revealed that exposure groups treated using MDTM exhibited a higher survival rate [HR = 0.84, 95% CI (0.76–0.92), P = 0.0004] with moderate heterogeneity (I2 = 68%, p = 0.01). For two studies that examined the effect of MDTM on the survival rate for patients specifically with stage IV HNC, MDTM did not produce any statistically significant improvement in survival rates [HR = 0.81, 95% CI (0.59–1.10), p = 0.18]. Conclusions: The application of MDTM based on conventional surgery, radiotherapy, and chemotherapy improved the overall survival rate of patients with HNC. Future research should examine the efficacy of MDTM in patients with cancer at different stages.